2007
DOI: 10.1039/b618943a
|View full text |Cite
|
Sign up to set email alerts
|

Reversible folding–unfolding, aggregation protection, and multi-year stabilization, in high concentration protein solutions, using ionic liquids

Abstract: We report the reversible thermal unfolding/refolding, and long period stabilization against aggregation and hydrolysis, of >200 mg ml(-1) solutions of lysozyme in ionic liquid-rich, ice-avoiding, solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
194
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(204 citation statements)
references
References 24 publications
7
194
3
Order By: Relevance
“…Fujita et al 30 have recently reported that the protein cytochrome c is remarkably stablilized in solution in a nontoxic dihydrogen phosphate IL, and we have found 31 that lysozyme in It is well-known from standard biological concentration solution studies that each protein has pH range in which its native state is most preferred and that deviations from that pH range can affect its folding energy and its stability against such undesirable behavior as aggregation, and recently, fibrillization. It might be expected that the proton activity of the solvent will exert a strong effect on the stability of proteins in the ionic liquid protective solution, and this is verified by our findings, 32 which are shown in Figure 12.…”
Section: Proton Activity and Protein Stabilization In Pilssupporting
confidence: 52%
“…Fujita et al 30 have recently reported that the protein cytochrome c is remarkably stablilized in solution in a nontoxic dihydrogen phosphate IL, and we have found 31 that lysozyme in It is well-known from standard biological concentration solution studies that each protein has pH range in which its native state is most preferred and that deviations from that pH range can affect its folding energy and its stability against such undesirable behavior as aggregation, and recently, fibrillization. It might be expected that the proton activity of the solvent will exert a strong effect on the stability of proteins in the ionic liquid protective solution, and this is verified by our findings, 32 which are shown in Figure 12.…”
Section: Proton Activity and Protein Stabilization In Pilssupporting
confidence: 52%
“…(i) Kill bacteria (O'Toole et al 2012); (ii) Extract, purify, and even store DNA at ambient temperature (Clark et al 2015(Clark et al , 2016; (iii) Stabilize proteins and enzymes Venkatesu 2014, Kumar et al 2017); (iv) Assist or prevent protein amyloidogenesis, and in some cases even return amyloid fibers to functional proteins (Byrne et al 2007, Byrne and Angell 2008, 2009);…”
Section: Introductionmentioning
confidence: 99%
“…Multi-lamellar structures can also be formed Fig. 1 Chemical sketches of some selected RTILs cations: (a),(b),(c) the most common imidazolium and pyrridinium RTIL cations; (d),(e) the doubletail lipid-mimic imidazoliumbased RTILs (Wang et al 2015a); (f),(g) the ethylammonium and guanidinium RTIL cations that help and contrast protein amyloidogenesis, respectively (Byrne et al 2007, Byrne and Angell 2008, 2009); (h) a phosphonium-based RTIL cation; and (i),(l) the choline and phosphocholine cations also used in RTILs made of amino acids (Benedetto et al 2014a) between RTILs and model biomembranes. Their aim is to determine the microscopic mechanisms behind their observed biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…ILs can be employed as a new class of solvents as many biological molecules (proteins, amino acids, DNA, sugars, and polysaccharides) can be solubilized in them without loss of their bioactivity (103). This specific property seems to be particularly relevant for the field of biosensing because ILs can provide an effective way to overcome the stability limitations of these sensors related to the limited temperature range and the very narrow pH range for protein stability in water (88).…”
Section: Ionic Liquids In Biosensorsmentioning
confidence: 99%
“…For instance, it was reported that cytochrome-c can be stored in hydrated choline dihydrogenphosphate for up to 18 months without losing its activity (102). Moreover, lysozyme was stabilized against denaturation during thermal cycles in aqueous media containing an equal mass fraction of ethylammonium nitrate while the unfolding/refolding of the protein is not possible when the IL was not added (103). Yang et al (104) first demonstrated the use of ILs as electrolytes for the development of organic electrochemical transistors (OECTs) for glucose sensing.…”
Section: Ionic Liquids In Biosensorsmentioning
confidence: 99%